Design, preparation and in vitro characterizations of fluconazole loaded nanostructured lipid carriers (Brazilian Journal of Pharmaceutical Sciences, 2020)
Present study was aimed to prepare and characterize fluconazole loaded nanostructured lipid carriers (FLZ-NLCs) for the treatment of fungal infections. Fungal infections are tremendously widespread and are the often faced dermatological condition worldwide. FLZ-NLCs was prepared by ultrasonication emulsion technique using stearic acid (SA) as solid lipid, castor oil as liquid lipid and tween 20 as a surfactant. The mean diameter of optimized FLZ-NLCs were found to be 359.15 ± 9.83 nm. The drug content and entrapment efficiency of NLCs was found to be 102.97 ± 7.45% and 87 ± 0.59%, respectively. In vitro drug release studies of FLZ-NLCs showed 37.34 ± 2.08% drug release over a period of 72 h. The above studies confirmed the prepared FLZ-NLCs may be useful for the treatment of fungal infections.